An International Collaboration towards Transformed Engineering Practice in Digital Earth. Issue 1 (June 2020) - Desha, C; Caldera, S; Fukui, H; Yasumoto, S
Abstract: Building on an appreciation of the 'Time Lag Dilemma' (previously published by the first author) and drawing on lived experiences (2017-18), the authors briefly describe the course and its assessment items. The authors also reflect on the benefits for academics in both universities to build capacity for embedding Digital Earth related knowledge and skills within their own coursework. The success of the course has immediate implications for ISDE community collaboration and capacity building within higher education, and more broadly bridging the gap between engineering and geospatial disciplines in the workplace. It is clear that the education sector has a key role to play in improving capacity to use digital and spatial information for meaningful enquiry and problem-solving.